Assessing How Energy Trade Shapes Indonesia's Foreign Exchange Reserves - Sunarta, Sunarta; Permana Yusuf, Budi; Fadhilah, Ash Shoffi Hana; Wibowo, Bagus Pamungkas (Universitas Muhammadiyah Prof. DR HAMKA., 2023)
Foreign exchange reserves are the guardians of macroeconomic stability and the country's financial system in supporting Indonesia's economic recovery. This research aims to examine the impact of rising Oil and Gas Exports (Export MIGAS) and Non-Oil and Gas Imports (Import Non-MIGAS) on Indonesia's foreign exchange reserves, as well as the prospects for these variables in the future. This study uses data from 2006-2021 obtained from the Badan Pusat Statistik (BPS). This study uses an analysis using the Ordinary Least Square (OLS) Model, and the Error Correction Model (ECM) method through the Augmented Dickey-Fuller test. Tests include stationarity, cointegration, Adjusted R-squared, t-test, and f-test. This study applies a research method that focuses on analyzing Indonesia's gas export and non-oil import data over the past 16 years as part of an evaluation of the country's foreign exchange reserves. The results of the study state that Export MIGAS and Non-Oil and Gas Imports (Import Non-MIGAS) have no influence on Indonesia's foreign exchange reserves in the short term, while in the long term, Export MIGAS have a negative influence on foreign exchange reserves and Import Non-MIGAS) have a positive influence on Indonesia's foreign exchange reserves